2019
DOI: 10.1093/molbev/msz039
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Histones H2A/H2B and Variant Hv1 in Tetrahymena thermophila Reveals an Ancient Network of Chaperones

Abstract: Epigenetic information, which can be passed on independently of the DNA sequence, is stored in part in the form of histone posttranslational modifications and specific histone variants. Although complexes necessary for deposition have been identified for canonical and variant histones, information regarding the chromatin assembly pathways outside of the Opisthokonts remains limited. Tetrahymena thermophila , a ciliated protozoan, is particularly suitable to study and unravel the chromati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 100 publications
(134 reference statements)
2
31
0
Order By: Relevance
“…Tetrahymena thermophila, a unicellular eukaryotic model system, provides an excellent system to study the functional conservation or diversification of chromatin-related and gene expression regulatory complexes [20,21]. The Tetrahymena genome encodes an Rpb1 (human POLR2A; yeast RPO21) that lacks canonical heptad repeats at its CTD, a feature that is shared among all ciliates ( Figures 1A and S1A).…”
Section: Rpb1 Lacks Canonical Ctd Heptad Repeats In Tetrahymenamentioning
confidence: 99%
“…Tetrahymena thermophila, a unicellular eukaryotic model system, provides an excellent system to study the functional conservation or diversification of chromatin-related and gene expression regulatory complexes [20,21]. The Tetrahymena genome encodes an Rpb1 (human POLR2A; yeast RPO21) that lacks canonical heptad repeats at its CTD, a feature that is shared among all ciliates ( Figures 1A and S1A).…”
Section: Rpb1 Lacks Canonical Ctd Heptad Repeats In Tetrahymenamentioning
confidence: 99%
“…Previously the Allis lab demonstrated that Hv1, like Ibd1, localizes to the MAC of growing cells implicating Hv1 in transcription (Wenkert and Allis, 1984). Tt SWR-C was defined by the intersection of common proteins in Ibd1 and Swc4 AP-MS (Saettone et al, 2018;Ashraf et al, 2019) with clear orthologs identified for Swr1, Yaf9, Rvb1, RvB2, Swc2, Swc4, and Swc5. AP-MS of Hv1 co-purified Swr1, Swc2, Arp5, and Rvb1 (Ashraf et al, 2019), consistent with Tt SWR-C function in the deposition of Hv1.…”
Section: Group II Brd Proteinsmentioning
confidence: 99%
“…Tt SWR-C was defined by the intersection of common proteins in Ibd1 and Swc4 AP-MS (Saettone et al, 2018;Ashraf et al, 2019) with clear orthologs identified for Swr1, Yaf9, Rvb1, RvB2, Swc2, Swc4, and Swc5. AP-MS of Hv1 co-purified Swr1, Swc2, Arp5, and Rvb1 (Ashraf et al, 2019), consistent with Tt SWR-C function in the deposition of Hv1. In yeast, the NuA4 HAT acetylates H4 which recruits SWR via the BRD-containing Bdf1 subunit to deposit Htz1 (Durant and Pugh, 2007;Altaf et al, 2010).…”
Section: Group II Brd Proteinsmentioning
confidence: 99%
See 2 more Smart Citations